The unreal and the real. Volume one, Where on earth : selected stories of Ursula K. Le Guin - Le Guin, Ursula K., 1929-2018 (Small Beer Press, 2012)
Where on Earth explores Le Guin's earthbound stories which range around the world from small town Oregon to middle Europe in the middle of revolution to summer camp.Companion volume Outer Space, Inner Lands includes Le Guin's best known nonrealistic stories.